A portrayal of violence, obstacles and agency of Muslim female characters in the novels, Woman at Point Zero and My Feudal Lord - Meem, Tabinda (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2017.